In Situ Transformation of Hydrogen-Evolving CoP Nanoparticles: Toward Efficient Oxygen Evolution Catalysts Bearing Dispersed Morphologies with Co-oxo/hydroxo Molecular Units - Ryu, Jaeyune; Jung, Namgee; Jang, Jong Hyun; Kim, Hyoung-Juhn; Yoo, Sung Jong (AMER CHEMICAL SOC, 2015)
Reported herein is elucidation of a novel Co-based oxygen evolution catalyst generated in situ from cobalt phosphide (CoP) nanoparticles. The present CoP nanoparticles, efficient alkaline hydrogen-evolving materials at the cathode, are revealed to experience unique metamorphosis upon anodic potential cycling in an alkaline electrolyte, engendering efficient and robust catalytic environments toward the oxygen evolution reaction (OER). Our extensive ex situ characterization shows that the transformed catalyst bears porous and nanoweb-like dispersed morphologies along with unique microscopic environments mainly consisting of discrete cobalt-oxo/hydroxo molecular units within a phosphate-enriched amorphous network. Outstanding OER efficiency is achievable with the activated catalyst, which is favorably comparable to even a precious iridium catalyst. A more remarkable feature is its outstanding long-term stability, superior to iridium and conventional cobalt oxide-based materials. Twelve-hour bulk electrolysis continuously operating at high current density is completely tolerable with the present catalyst.
Keywords: WATER OXIDATION CATALYST; RAY PHOTOELECTRON-SPECTROSCOPY; COBALT PHOSPHIDE NANOPARTICLES; NITROGEN-DOPED GRAPHENE; ACTIVE EDGE SITES; CARBON NANOTUBES; NEUTRAL PH; ASTERISK-ASTERISK; NANOWIRE ARRAYS; IRIDIUM OXIDE